Bridge Collapse in Mutsu, Aomori Prefecture, Japan in 2021 - Hiroshi Takebayashi; Masaharu Fujita (Journal of Flood Risk Management)
ABSTRACT On August 9–10, 2021, the Koakagawa Bridge in Mutsu, Aomori Prefecture, Japan, collapsed owing to the flood caused by a tropical cyclone. In this study, the cause of the collapse was examined. The characteristics of flood inundation with bypassing flows and countermeasures for bank erosion due to channel blockage by driftwood were investigated based on field surveys and numerical simulations. The scouring of the bed around the bridge pier was found to be the cause leading to bridge failure. Channel blockage owing to driftwood would have caused flood inundation and damage to the left bank, the top of the bank is bare of sediment, by forming a bypassing flow. However, the surface of the right bank on which the bypassing flow with high velocity formed was covered with concrete; therefore, bank erosion did not occur. These results indicate that to prevent bank erosion caused by bypassing flows during floods, it is important to protect banks downstream of the bridge using non‐erosive materials. Only a small area, where bypassing flows form and non‐dimensional shear stress is larger than 0.05, is sufficient for protection. It is also important to predict bed degradation characteristics around piers and banks, especially when the bed material is small.